Crack path simulation in a particle-toughened interlayer within a polymer composite laminate. (14th September 2016) - Borstnar, G.; Mavrogordato, M.N.; Yang, Q.D.; Sinclair, I.; Spearing, S.M.
Abstract: With recent advances in computational resources and the development of arbitrary cracking methods, such as the Augmented Finite Element Method (A-FEM), more complex simulations can now be represented featuring multiple interacting cracks. It has been established that Mode I crack propagation in particle-toughened interlayers within some toughened Carbon Fibre Reinforced Polymer (CFRP) laminates involves a discontinuous process zone, rather than a distinct crack tip. This results from multiple cracks forming ahead of the main crack that subsequently coalesce, leaving behind bridging ligaments that may then provide traction across the crack flanks. An idealised two-dimensional A-FEM model is presented in this work, which represents the 'particles' as one-dimensional cohesive regions. The model shows that variables such as particle spacing, distribution, strength and toughness, and fibre interface strength can be tailored in order to maintain the crack path within the interlayer. This competition between crack paths is important, as a reduction in composite toughness is reported when the crack path migrates to the fibre interface. The simulations are complemented by time-resolved Synchrotron Radiation Computed Tomography (SRCT) data, which identify the chronology of the damage processes, along with the effects of particle distribution on the crack path and the formation of bridging ligaments.